2014
DOI: 10.1111/bjep.12050
|View full text |Cite
|
Sign up to set email alerts
|

If one goes up the other must come down: Examining ipsative relationships between math and English self‐concept trajectories across high school

Abstract: Implications for self-concept theory, interventions, and statistical methods for the study of growth are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Previous studies have reported moderate to relatively high stability coefficients in adolescent students for academic self-concept (e.g., Shavelson and Bolus, 1982 ; Eccles et al, 1989 ; Marsh et al, 2005 ; Frenzel et al, 2006 ; Möller et al, 2011 ; Pinxten et al, 2014 ; Musu-Gillette et al, 2015 ; Parker et al, 2015 ), academic interest (e.g., Watt, 2000 ; Köller et al, 2001 ; Marsh et al, 2005 ; Frenzel et al, 2006 , 2010 ; Musu-Gillette et al, 2015 ), intrinsic motivation (a construct that is conceptually close to academic interest; e.g., Gottfried et al, 2001 ), and enjoyment (the emotional component of academic interest; Pinxten et al, 2014 ) in mathematics or verbal subjects. For example, Frenzel et al ( 2010 ) found 1-year stabilities in interest in mathematics ranging from 0.54 to 0.65 between Grades 6 and 9.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have reported moderate to relatively high stability coefficients in adolescent students for academic self-concept (e.g., Shavelson and Bolus, 1982 ; Eccles et al, 1989 ; Marsh et al, 2005 ; Frenzel et al, 2006 ; Möller et al, 2011 ; Pinxten et al, 2014 ; Musu-Gillette et al, 2015 ; Parker et al, 2015 ), academic interest (e.g., Watt, 2000 ; Köller et al, 2001 ; Marsh et al, 2005 ; Frenzel et al, 2006 , 2010 ; Musu-Gillette et al, 2015 ), intrinsic motivation (a construct that is conceptually close to academic interest; e.g., Gottfried et al, 2001 ), and enjoyment (the emotional component of academic interest; Pinxten et al, 2014 ) in mathematics or verbal subjects. For example, Frenzel et al ( 2010 ) found 1-year stabilities in interest in mathematics ranging from 0.54 to 0.65 between Grades 6 and 9.…”
Section: Introductionmentioning
confidence: 96%
“…For example, with such dimensional comparison processes, positive evaluations in one academic subject may yield lower self-evaluations in other subjects (i.e., contrast effect). Such dimensional comparison processes may have important consequences for students' development, namely, that self-concept in one subject will have a negative effect on change in self-concept in other subject (see Parker et al, 2015 ). For example, the reciprocal internal/external frame of reference model (RI/E model; Möller et al, 2011 ) predicts small negative effects of academic self-concept on subsequent academic self-concept in noncorresponding subjects (Niepel et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Not only identifying important aspects of achievement growth over time, they also provide guidance on how to conduct analyses across an extended time period. Parker, Marsh, Morin, Seaton, and Van Zanden () also provide analytical and substantive guidance regarding trajectories over time. They track high school students' academic self‐concept across 10 time waves with an interest in testing core contentions under the internal–external (IE) frame of reference model of self‐concept.…”
Section: Introductionmentioning
confidence: 99%
“…In educational psychology, there has been increasing interest in growth approaches to student development, including value‐added models, modelling of academic trajectories, growth motivation orientations, and growth goals (Anderman, Anderman, Yough, & Gimbert, ; Anderman, Gimbert, O'Connell, & Riegel, ; Betebenner, , ; Briggs & Betebenner, ; Elliot, Murayama, Kobeisy, & Lichtenfeld, ; Elliot, Murayama, & Pekrun, ; Harris, ; Martin, , ; Martin & Liem, ; Masters, ; Parker, Marsh, Morin, Seaton, & Van Zanden, ). At the same time, educational psychology and other psychological disciplines have emphasized the concept of ‘growth mindset’, with particular focus on implicit theories about ability and intelligence (Dweck, , , ).…”
Section: Introductionmentioning
confidence: 99%